PERAN KOMUNIKASI INTERNAL DALAM MENINGKATKAN EFEKTIVITAS IMPLEMENTASI PERUBAHAN - Parikesit S, Bangun; Aditya P, Yoga; Dwi S, Daffa; Quthbir R, Daffa; Revelyn F, Haykel; Haludin, Guntur (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Internal communication plays a vital role in the successful implementation of change in an organization. However, many organizations face challenges in ensuring effective communication among all stakeholders, which impacts the level of acceptance and success of change. This study aims to analyze how internal communication strategies can improve the effectiveness of change implementation in the context of organizational management. The methodology used is a qualitative approach with a case study at Nokia, where data were collected through in-depth interviews, observations, and analysis of related documents. This study also adopts a strategic communication framework to evaluate the internal communication practices that have been implemented. The expected results of this study are the identification of effective internal communication strategies, such as information transparency, the use of appropriate communication media, and the active involvement of leaders in conveying the vision of change. This study is expected to contribute to the development of change management theory, as well as offer practical guidance for organizations in improving the success of change implementation through better internal communication management